2021
DOI: 10.7196/samj.2021.v111i3.14669
|View full text |Cite
|
Sign up to set email alerts
|

Economic growth as an underlying probable systemic driver for childhood obesity in South Africa: A Joinpoint regression and ecological analysis over 10 years

Abstract: The emergence of non-communicable diseases (NCDs), including type 2 diabetes, hypertension and obesity, in low-to middleincome countries (LMICs) has raised global concerns. [1,2] A need to reprioritise use of limited resources, capacity and infrastructure in LMICs is important. In view of limited resources to deal with emerging NCDs, prevention seems the only feasible and sustainable approach. Communicable diseases have been the priority for most LMICs, but shifts in disease burden are being observed. These sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(27 citation statements)
references
References 27 publications
(35 reference statements)
0
27
0
Order By: Relevance
“…The likely reasons for this study finding in Nigeria and South Africa are that women with higher education are more likely to have a higher socio-economic status and material resources and have ready access to energy-dense nutrition and sugary beverages, as well as a more sedentary paying job. Women from wealthier households, having weight above average, and presently living with partner had increased odds of being overweight or obese, among women from Nigeria [ 9 , 22 ] and South Africa [ 14 , 15 ]. Moreover, as the number of children increases, the odds of being overweight or obese were decreased, and smoking of cigarettes also increased the likelihood of being underweight among South African women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The likely reasons for this study finding in Nigeria and South Africa are that women with higher education are more likely to have a higher socio-economic status and material resources and have ready access to energy-dense nutrition and sugary beverages, as well as a more sedentary paying job. Women from wealthier households, having weight above average, and presently living with partner had increased odds of being overweight or obese, among women from Nigeria [ 9 , 22 ] and South Africa [ 14 , 15 ]. Moreover, as the number of children increases, the odds of being overweight or obese were decreased, and smoking of cigarettes also increased the likelihood of being underweight among South African women.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as increased adoption of more westernized diets and the rise in sedentary behavior, owing to modernization, improved transport systems, and easy convenient access to unhealthy fast foods, are associated with over-weight/obesity and its related-health problems in South Africa [ 6 , 13 ]. Studies have documented that the body mass index (BMI) cutoffs for women and men are 29.2 and 23.6 respectively, whereby 68% of women are overweight/obese while 3% are underweight, as two-thirds of women (59%) have a BMI in the standard range [ 14 ]. According to the South Africa Demographic Health Survey (SADHS), the trend analysis indicated that the mean BMI among women aged 15 and older has increased from 27.3 in 1998 to 29.2 in 2016, and the prevalence of overweight/obesity among women of childbearing age rose from 56% to 68%, with a decreased prevalence of underweight from 6% to 3% [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Signatory to international and regional declarations; explicit policies and commitments for KPs. 4 , 10 …”
Section: Resultsmentioning
confidence: 99%
“…Several mechanisms exist for overseeing programme activities, including PRC and the M&E team at SANAC, which is responsible for producing the GAM reports. 6 , 10 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation